Ki tanít? roma pedagógusok vidéki oktatási terekben = Who teaches? : Roma professionals in rural educational spaces - Fejős Anna (Belvedere Meridionale Szeged, 2018)
While there is an increasing number of Roma students in basic education in Hungary, the teacher force hardly changes: most teachers are of majority middle-class background. Meanwhile, we know little about the experiences of the few Roma in the profession. The paper shows, through the analysis of interviews, the career trajectories of ten Roma pedagogues, along with some aspects of their professional practice. The wish to lead by example is strong in all narratives, and it is embedded in the teachers’ way of educating pupils, conveying curricula, and keeping contact with families. These are also the areas, where in addition to professional expertise, interviewees build upon their ethnic belonging. Sometimes the two compliment each other, while in other cases conflicts arise due to differing expectations. The analysis reveals that Roma pedagogues can actively shape the educational practices.
Keywords: Társadalomtudományok; Oktatástudomány